Stabilization of protein by biocompatible nanoparticles of silver - Singh S.K.; Shrivastava S.; Nayak M.K.; Sinha A.S.K.; Jagannadham M.V.; Dash D. (My University, 2025)
Extraordinary optical properties, biocompatibility, and chemical stability make silver nanoparticles ideal candidate for application in bio-medical field. They are stabilized by virtue of their protein conjugation property. Here we report that in addition to protein conjugation nano silver also has excellent protein stabilization property. Formation of bioconjugate with nano silver was coupled with enhanced stabilization of protein secondary and tertiary structures, thereby retaining native conformation and preventing denaturation which is a rare phenomenon with other nanomaterials. This would be of immense significance for applications of conjugated peptides where the protein functions can be utilized. Using nano silver-BSA complex as model we have characterized optimal conditions for bioconjugation and mapped protein conformational changes ensued upon formation of conjugate. Conjugated BSA showed more resistance towards thermal denaturation as compared to its native counterpart. Our approach offers promise for designing of biologically functional, stable and controllable protein-silver nanoparticle composites. Copyright © 2009 American Scientific Publishers All rights reserved.